Funded pensions - a remedy for an ageing society? - Dybał, Mariusz (University of Wroclaw. Faculty of Law, Administration & Economics, 2012)
In this article the author demonstrates that over the coming decades the EU, the OECD and many countries will face a significant acceleration of demographic ageing due to three main factors: the baby-boom generation reaching retirement age, continuing increases in life expectancy and decreased fertility since the 1970s. Eventually, all three factors mentioned will combine to produce a major financial challenge for pension systems in the coming years, when the number of pensioners will rapidly increase and the size of the working-age population will diminish. According to the data gathered, to prevent this situation, countries all over the world are reforming their pension systems. Most are reforming to decrease the fiscal costs of their existing systems. A few relatively young countries are establishing new systems or are increasing the generosity of their current systems. Nevertheless, the majority of the pension reforms are dealing with an existing pay-as-you-go defined benefit system, rather than reform of the overall system of pension provision. However, while these minor reforms alleviate some of the fiscal burden, fiscal problems will reappear in the long term. The only way to effectively solve the pension system issue on a permanent basis is to move toward the fully-funded defined contribution reforms currently underway in Latin America, Australia, Central and Eastern Europe and under consideration in a variety of other countries
Keywords: emerytury kapitałowe; starzenie się społeczeństwa